Comparative study on cost evaluation and network visualization of particle accelerator components for heavy ion inertial fusion. (May 2016) - Inoue, A; Takahashi, K; Sasaki, T; Kikuchi, T; Harada, Nob; Barnard, J J
Abstract: By visualizing accelerator system components in heavy ion inertial fusion, the connection between the components becomes clear. We clarify an influential component on the entire cost by the relation of node connections due to the visualization result. Since a low cost component affects a high cost component, not only the cost estimation but also the relation between the components is considerable and important issue. A cost estimation result changing with an induction core cost indicates no influences in the rate of details.